Preparation of Balanced Scorecard as Performance Measurement Instrument in PP. Kecap Maja Menjangan - Irawan, Arie Wibowo; Mohamad Zaki, Nur Amalina (Journal of Social Transformation and Regional Development, 2022)
This study aims to (1) formulate and describe the BSC strategy map under the company’s vision, mission, and strategy, (2) formulate the design of performance measurement system based on the BSC concept (3) measure the performance that has been achieved with BSC approach and analyze the results. The lag of indicators used by PP. Kecap Maja Menjangan is a net profit/loss margin and sales growth rate and a level of customer satisfaction index regarding the quality, price, and reputation of the product from the customer perspective. The internal business process is measured through revenue per cost (R/C) growth and the proportion of new product revenue to TR, while the level of employee satisfaction is measured through initiatives, risk tolerance, direction, integration, supervision, identity and motivation, and reward system as the lag indicator for learning and growth. The final score of 72,91 percent indicates the good overall performance of the company (although not optimal). The company performed well on all three non-financial perspectives marked by achievements above 75 percent. While the achievement of a financial perspective that showed below average results in this research period indicates the influence of external factors outside the analysis (such as the increase in the price of raw materials and fuel) that indirectly affect financial performance. Implementation of BSC plan on PP. Kecap Maja Menjangan could be done with the following stages: (1) Review of BSC design, (2) communicate the design and setting individual objectives, (3) strengthen the annual plan and budget, and (4) conduct monthly evaluations. The failure and success of BSC implementation should be viewed positively because this approach requires continuous improvement as a process towards learning organization.